Syrian Civil War?s effects on Turkish school children: prevalence and predictors of psychopathology - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2019)
ObjectivesThe Syrian Civil War forced millions into asylum in neighbouring countries. Refugees/asylum seekers have elevated risk for psychopathology with the most important being post-traumatic stress disorder (PTSD). Subjective experiences and symptoms of the hosting populations which have also experienced similar traumas have received relatively little attention up to now. We aimed to evaluate the effects of Syrian Civil War in terms of psychopathology, traumatic experiences and PTSD on Turkish primary school students living in Suru? which is on the border with Syria and hosts a large population of asylum seekers.MethodsTwo randomly selected schools operating in the district were included in the study. Sociodemographic Data forms, Child Behaviour Checklist (CBCL), Children?s Post-traumatic Reaction Index (CPRI) were used for evaluations. Data were analysed with SPSS 23.0. P was set at 0.05 (two-tailed).ResultsMost common traumatic experiences via parental report were witnessing explosions (26.9%), witnessing injuries of extended family/relatives (21.8%) and witnessing deaths of acquaintances (17.9%). Lifetime traumatic events and lifetime self-injurious behaviour in children via parental report were 26.9% and 19.9%; respectively. Of 156 students (53.2% male) with a mean age of 8.8 years (S.D.?=?1.3), 13.5% obtained externalizing scores, 11.0% obtained internalizing scores and 13.5% obtained total scores in the clinical range of CBCL. 98.7% reported PTSD symptoms in moderate and above severity in CPRI. Most common traumatic experiences reported by children included hearing explosions/gunshots (17.3%), damage to residences (17.3%), and witnessing deaths of extended family/ acquaintances (12.8%). Female gender (p?=?.00), witnessing loss of family members/acquaintances in Syrian Civil War (p?=?.01) and clinically significant PTSD symptoms in CPRI.ConclusionChildren in communities hosting Syrian refugees/asylum seekers may also have elevated symptoms of PTSD and female gender may be a risk factor for those symptoms.
Keywords: Refugee; post-traumatic stress disorder; PTSD; mental health; trauma; psychopathology; POSTTRAUMATIC-STRESS-DISORDER; REFUGEES